Officers, charter, by-laws, rules, members. - University Club of Philadelphia (Philadelphia [Pa.] : Printed by George H. Buchanan and Co., 1900)
The University Club of Philadelphia [Pa.], is a social club of college and university graduates for advancing the interests of liberal education.
Mode of access: Internet.
Keywords: University Club of Philadelphia -- Directories; University Club of Philadelphia -- Rules and practice; University Club of Philadelphia -- By-laws.; University Club of Philadelphia -- Charters; Rules; Directories; Charters and articles of incorporation; By-laws